Diabetic Vitrectomy: Less is More - Sallam, Ahmed B. (Pakistan Journal of Ophthalmology, 2017)
Tractional retinal detachment (TRD) that threatens or involves the macula, is the second most common indication for pars plana vitrectomy in diabetic eyes1. The primary goals of vitreous surgery in tractional diabetic detachment include removal of vitreous hemorrhage, and the elimination of antero-posterior and tangential macular traction, thus stabilizing and increasing the vision. Removing all membranes is believed to reduce the frequency of postoperative re-bleeding, and the risk of epiretinal membranes/TRD recurrences. In proliferative diabetic retinopathy (PDR), fibrovascular tissue extends along the posterior hyaloid surface. This proliferation often causes changes in the vitreous gel that result in further traction on the retinal neovessels.